Factors Associated With Adherence To Iron Supplementation Among Pregnant Women - Septi Indah Permata Sari (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2019)
In Indonesia, the contribution of anemia towards maternal mortality is estimated to reach 10% up to 20%. The effort of the government to overcome anemia focuses on iron supplementation program since 1974, but the prevalence of anemia in pregnant mother still relatively high. The factor is discompliance in taking medicine. This study aimed to analyse the factors that related to the compliance of pregnant mother in taking the iron tablet at the Tegalrejo Community Health Centers, Yogyakarta. This research used mixed methods by using sequential explanatory strategy. The quantitative sample is taking used consecutive sampling technique, which presented 81 pregnant mothers and intensity sampling for qualitative research presented 13 informants. Based on the result of the analysis, the factors which related to the Compliance of pregnant mother in taking iron tablet were knowledge (p=0,000), husband support (p=0,000) and midwife support (p=0,000). The most significant Exp(B) score was the variable of husband support, which was 15.297. It concluded that pregnant mothers who got support from their husbands would be 15.297 times more significant to obey in taking the iron tablet. Based on the interview of the informants showed that both husband and midwife support in taking an iron tablet. The factors related to the Compliance of pregnant mother in taking the iron tablet at clinic government Tegalrejo, Yogyakarta was knowledge, husband and midwife supports